2013
DOI: 10.1136/bjsports-2013-092558.12
|View full text |Cite
|
Sign up to set email alerts
|

Conservative Treatment of Total Proximal, Non-Avulsion, Hamstring Muscle - Rupture, in High Level Athletes

Abstract: BackgroundHamstring muscle injuries are notoriously found among the most common causes of abstinence and delayed return to sport, in a variety of track, field and other high level athletes. In this respect we present our experience of conservative treatment of total proximal, non-avulsed hamstring rupture in high-level track, field and other athletes and application of an integrated rehabilitation protocol.MethodsEleven high level athletes, nine men and two women, were diagnosed with sub/ total proximal, non-a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…A previous systematic review done by Harris et al 22 reported a return to sports rate at a preinjury level of 82% following surgical repair but did not report data concerning hamstring strength, patient satisfaction rates, and functional outcome scales, which prevents further comparison. For comparison, Sallay et al 44 and Malliaropoulos et al 36 reported return to sports rates after nonoperative management of 58% and 100%, respectively. Studies included in our systematic review reported that surgical management of proximal hamstring avulsions leads to varying rates of return to sport (76%-100%) and return to preinjury activity level (55%-100%), high scores on functional outcome scales, and high patient satisfaction (88%-100%).…”
Section: Overview Of Surgical Repairmentioning
confidence: 99%
See 1 more Smart Citation
“…A previous systematic review done by Harris et al 22 reported a return to sports rate at a preinjury level of 82% following surgical repair but did not report data concerning hamstring strength, patient satisfaction rates, and functional outcome scales, which prevents further comparison. For comparison, Sallay et al 44 and Malliaropoulos et al 36 reported return to sports rates after nonoperative management of 58% and 100%, respectively. Studies included in our systematic review reported that surgical management of proximal hamstring avulsions leads to varying rates of return to sport (76%-100%) and return to preinjury activity level (55%-100%), high scores on functional outcome scales, and high patient satisfaction (88%-100%).…”
Section: Overview Of Surgical Repairmentioning
confidence: 99%
“…{ Nonoperative management of proximal hamstring avulsions mainly comprises rest, icing, and exercises with a gradual return to (athletic) activities 10 and appears to lead to conflicting results. Sallay et al 45 presented 12 cases, of which 58% returned to sports at a lower level, while Malliaropoulos et al 36 presented 11 high-level athletes with a 100% return to sports rate.…”
mentioning
confidence: 99%
“…Sallay et al [9] reported on 12 cases of proximal hamstring avulsions treated nonoperatively with only 58% of individuals returning to sport, and all at a lower activity level. In a similar study, Malliaropoulos et al [10] reported on 11 high-level athletes treated nonoperatively with a 100% return to sport. In a systematic review, Harris et al [11] described a return to sport rate of 82% in operative groups versus only 14% in nonoperative groups.…”
Section: Discussionmentioning
confidence: 98%